Impact of Tyrosine Kinase Inhibitors (TKIs) Combined With Radiation Therapy for the Management of Brain Metastases From Renal Cell Carcinoma - Khan, Muhammad; Zhao, Zhihong; Arooj, Sumbal; Liao, Guixiang (Frontiers in Oncology, 2020)
Background Targeted therapy has transformed the outcome for patients with metastatic renal cell carcinoma. Their efficacy and safety have also been demonstrated in brain metastatic RCC. Preclinical evidence suggests synergism of radiation and tyrosine kinase inhibitors. Consequently, several studies have compared their efficacy in the treatment of RCC brain metastases to the era of brain management with surgery/radiation only. Objectives We seek to systematically review and meta-analyze the results of those studies that involved comparative intervention groups of brain management; TKIs, and never used TKIs. Methods & Materials Online databases (PubMed, EMBASE, Cochrane library, and ClinicalTrials.gov) were searched for comparative studies. Overall survival as the primary outcome of interest, and local brain control, distant control, and adverse events as secondary outcomes of interest were recorded for meta-analysis. Hazard ratios were pooled together using Review Manager 5.3. Fixed effects or random effects model were adopted according to the level of heterogeneity. Subgroup analysis included studies that involved SRS as the local treatment of management. Results Overall 7 studies (n=897) were included for meta-analysis. TKI use was associated with better survival (HR 0.60 [0.52, 0.69], p<0.00001) and local brain control (HR 0.34 [0.11, 0.98], p=0.05). SRS subgroup also revealed significantly better survival (HR 0.61 [0.44, 0.83], p=0.002) and local brain control (HR 0.19 [0.08, 0.45], p=0.0002). Distant brain control (HR 0.95 [0.67, 1.35], p=0.79) and brain progression free survival were unaffected (HR 0.94 [0.56, 1.56], p=0.80). Only one study (n=376) reported significantly greater 12-months cumulative incidence of radiation necrosis with TKI use within 30 days of SRS (10.9% vs 6.4%, p=0.04). Conclusions TKIs use in combination with SRS is safe and effective for treating RCC brain metastases. Larger randomized controlled trials are warranted to validate the results.